Perlindungan Hukum Korban Tindak Pidana Penyebaran Video Porno Ditinjau dari Undang-Undang Nomor 31 Tahun 2014 tentang Perlindungan Saksi dan Korban - Nafisa Aulia Nuha (Bandung Conference Series: Law Studies, 2024)
Abstract. Distribution of pornographic videos is a crime that often occurs and harms victims. Victims of the distribution of pornographic videos certainly experience long-term physical and psychological impacts. Therefore, victims need legal protection against the occurrence of these criminal acts. This research aims to determine legal protection for victims of criminal acts of distributing pornographic videos in Law Number 31 of 2014 concerning Protection of Witnesses and Victims and the implementation of physical-social rehabilitation assistance for victims of criminal acts of distributing pornographic videos. This research approach method is qualitative with a type of doctrinal legal research. The specifications of this research are descriptive analysis using a statutory approach and a case approach. Data collection was carried out by literature study and then analyzed using descriptive qualitative. Psychosocial rehabilitation is important for victims of criminal acts of distributing pornographic videos. This psychosocial rehabilitation is a form of legal protection obtained by victims of the distribution of pornographic videos as stipulated in Article 6 paragraph (1) letter b of Law Number 31 of 2014 concerning Protection of Witnesses and Victims. This psychosocial rehabilitation is provided to help victims overcome trauma, restore self-confidence, and improve the victim's quality of life. The implementation is carried out through several stages, namely evaluation and assessment, goal setting, intervention planning, intervention implementation, evaluation and revision, as well as long-term monitoring and support. This psychosocial rehabilitation is provided based on the LPSK's decision at the request of the victim of the distribution of pornographic videos. Abstrak. Penyebaran video porno menjadi tindak pidana yang seringkali terjadi dan merugikan korban. Korban penyebaran video porno tentu mengalami dampak fisik maupun psikis secara berkepanjangan. Oleh sebab itu korban membutuhkan perlindungan hukum atas terjadinya tindak pidana tersebut. Penelitian ini bertujuan untuk mengetahui perlindungan hukum terhadap korban tindak pidana penyebaran video porno dalam Undang-Undang Nomor 31 Tahun 2014 Tentang Perlindungan Saksi dan Korban dan implementasi bantuan rehabilitas phsyco-social terhadap korban tindak pidana penyebaran video porno. Metode pendekatan penelitian ini kualitatif dengan jenis penelitian hukum doktrinal. Spesifikasi penelitian ini deskriptif analisis dengan pendekatan perundang-undangan dan pendekatan kasus. Pengumpulan data dilakukan dengan studi pustaka dan kemudian dianalisis dengan deskriptif kualitatif. Rehabilitasi psikososial ini menjadi salah satu bentuk perlindungan hukum yang diperoleh korban penyebaran vidio porno sebagaimana ketentuan Pasal 6 ayat (1) huruf b Undang-Undang Nomor 31 Tahun 2014 tentang Perlindungan Saksi dan Korban. Rehabilitasi psikososial ini diberikan untuk membantu korban mengatasi trauma, mengembalikan rasa percaya diri, dan memperbaiki kualitas hidup korban. Adapun implementasinya dilakukan melalui beberapa tahapan yaitu evaluasi dan penilaian, penetapan tujuan, perencanaan intervensi, pelaksanaan intervensi, evaluasi dan revisi, serta pemantauan dan dukungan jangka panjang. Rehabilitasi psikososial ini diberikan berdasarkan keputusan LPSK atas permintaan pihak korban penyebaran vidio porno.